Bone mineral density and dual-energy x-ray absorptiometry - Marina Kanthack Paccini; Maria Fátima Glaner (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p92 The objective of this review article is to gather the relevant information on bone tissue and the validation and limitations of dual-energy X-ray absorptiometry. To this end, national and international studies indexed on the Pubmed, Lilacs and Nuteses databases were analyzed. The features discussed were: bone tissue maturation, bone tissue in different populations, the impact of intervention programs on bone tissue, dual-energy X-ray absorptiometry, and its validation and limitations. According to data found in the literature, certain observations can be made. Bone mineral density changes during the different stages of life, childhood, adolescence, adulthood and old age; it can also be influenced by race, sex, genetic factors and life style in addition to by age. The importance of monitoring bone mineral density, both to good health and to social and economic aspects of society, is evident. Studies have confirmed the efficacy of dual-energy X-ray absorptiometry for measuring body composition (bone, fat and muscle). However, in recent studies, although few in number, some limitations of using this equipment have been noted, which may affect its accuracy. It is therefore understood that there is a need for further studies into this subject, with the intention of defining the accuracy of this equipment.